Предмет: Алгебра,
автор: iris238554
разложите на множители (3+x)(x-3)-(3-x)²
Ответы
Автор ответа:
0
Так как (3 - x)^2 = (x - 3)^2, то перепишем так
(x + 3)(x - 3) - (x - 3)^2 =
= (x - 3)(x + 3 - (x - 3)) =
= (x - 3) (x + 3 - x + 3) =
= 6 (x - 3)
(x + 3)(x - 3) - (x - 3)^2 =
= (x - 3)(x + 3 - (x - 3)) =
= (x - 3) (x + 3 - x + 3) =
= 6 (x - 3)
Похожие вопросы
Предмет: Математика,
автор: elizaveta91278
Предмет: Українська мова,
автор: slepkotaras2108
Предмет: Английский язык,
автор: timurdzumanov14
Предмет: Математика,
автор: 955357
Предмет: Математика,
автор: anuar2010